Evaluation and redesign of VX Events' virtual exhibition interface for customer service improvement - Pua, Andre William S (Animo Repository, 2022)
A well-designed virtual exhibition can offer alternatives for the physical event. It opens up new opportunities for education, access to more information, interactive user participation, and so on. Usability is the degree to which a service, system, or product can be used effectively, efficiently, and satisfactorily by certain users. Through usability testing and HOQ, the visitor and exhibitor's average SUS score deviation of 15.33% and 18.58 % from a target of 68 resulted in the following three design factors as problems: Simplicity, Graphical Representation, and Organization with a total of 609 errors and an average VOC percentage importance of 56.95%, 29.2%, and 13.85% respectively. Usability test and House Of Quality 1 (HOQ1) was used to obtain usability testing results and the voice of customers, respectively. Once completed, development of alternatives, evaluation of alternatives will be used to determine the best solution for the proposed final design. Design of Experiment (DOE) was used in order to come up with various design alternatives for VX Events’ virtual platform. With a new interface design, the SUS score increased by 54.74% for the visitor's perspective and 81.26% for the exhibitor's perspective, both meeting the target score of 68. as a result of the new virtual website design. Moreover, with the new design, a total count of 189 of error was achieved. This reflects a decrease in error count by 71.60% for the visitor’s perspective and 66.22% for the exhibitor’s perspective. In addition, both perspectives resulted in having a p-value of less than 0.05 showing a statistically significant decrease. With the adoption of the new design, it is anticipated that the company will meet its KPI of 50% return visitors. Additional research is required, as well as improvements to the virtual exhibition's layout and proportions, in order to increase its use by a wider range of users and make up for other users' virtual display limitations, such as networking events and conferences.